Urine Cytology—Unveiling its True Potential - Arpana Dharwadkar; Nayonikha N. Deokar; Sushama Gurwale; Vidya Viswanathan (Medical Journal of Dr. D.Y. Patil Vidyapeeth)
Genitourinary tuberculosis (GUTB) is caused by the hematogenous spread of chronic latent pulmonary tuberculosis thus affecting the genital organs or urinary tract. Often there is an impediment in diagnosis due to simulation of symptoms and signs by another disease, usually a urinary tract infection or malignancy. Since GUTB is emerging as a remarkable public health problem in the developing world, early detection, prompt treatment, and long-term monitoring are needed to eradicate it. A simple urine cytology examination can detect granulomas and acid-fast bacilli on ZN stain which help to diagnose GUTB and an aggressive treatment can be easily avoided.